182k views
4 votes
How does -2x + x equal -x ?

User Lea
by
4.7k points

2 Answers

1 vote

Answer:

Explanation:

-2x + x could also be written as x - 2x, which is x(1 - 2), or -x. Here we can rearrange the terms as we wish (commutative property).

User Avmohan
by
5.2k points
3 votes

Answer:

See below.

Explanation:


-2x+x=-x

because we combine like terms. You will essentially ignore the x and just do -2 + 1, which is -1. So, the answer would be -1x which is simply just -x.

To see why we can combine like terms, use the distributive property. So we have:


-2x+x

This is the same thing as saying:


=(-2)x+(1)x

Factor out the x:


=x(-2+1)

Add:


=x(-1)

And simplify:


=-1x\\=-x

User Guitz
by
4.3k points